Budaya Konsumtif Makanan Jepang Onigiri dalam Kehidupan Remaja Di Kota Gresik - Cuk Yuana; Sukmawati Sukmawati (Mezurashii: Journal of Japanese Studies, 2022)
ABSTRACT The development of an increasingly advanced era with technology is developing rapidly, and facilitates the dissemination of information that makes foreign or foreign cultures enter a country. Especially the influence of foreign culture on food has changed the tastes of the Indonesian people. Like fast food, types of food that are easy to pack and practical. One of the practical foods in making or eating it is Onigiri. The method used in this research is a quantitative descriptive method. A method that aims to create an description of a research that uses numbers, starting from data collection, interpretation of the data as well as the appearance and results. Sample collection was carried out by distributing questionnaires in the form of online links to 100 adolescent respondents regarding the consumer Onigiri food in the city of Gresik. In this study using the Likert scale analysis model and spearman rank correlation. The results obtained from the Likert scale data, the most preferred type of onigiri flavor is "Onigiri Hot Tuna", followed by "Onigiri Chicken Mayo", then "Onigiri Chicken Teriyaki" with an interpretation rate of 46.53%, which means that the respondent's interest in onigiri is in the category “No. Like". The results of the Spearman rank test from 1 to 4 from the analysis show that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted that the first question and the second question have a significant correlation, meaning that respondents have tried to eat onigiri. Keywords: Onigiri, Onigiri Taste, Consumptive Culture